2023
DOI: 10.1002/eji.202149775
|View full text |Cite
|
Sign up to set email alerts
|

Eomesodermin‐expressing type 1 regulatory (EOMES+Tr1)‐like T cells: Basic biology and role in immune‐mediated diseases

Abstract: Type 1 regulatory (Tr1) T cells are currently defined all T cells with regulatory functions that lack FOXP3 expression and produce IL‐10. Tr1 cells are heterogeneous, and the different reported properties of Tr1‐cell populations have caused some confusion in the field. Moreover, understanding the role of Tr1 cells in immune‐mediated diseases has been hampered by the lack of a lineage‐defining transcription factor. Several independent studies indicated recently that the transcription factor Eomesodermin (EOMES)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…The upregulation in EOMES , a transcription factor involved in the T-cell exhaustion process in severe COVID-19 patients, in the comparison describing infected and not vaccinated cases, suggests that EOMES may play a role in the development of T-cell exhaustion, as described before [ 45 ]. It directly induces IFN-γ and cytotoxicity, enhances IL-10, and antagonizes alternative T-cell fates [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation in EOMES , a transcription factor involved in the T-cell exhaustion process in severe COVID-19 patients, in the comparison describing infected and not vaccinated cases, suggests that EOMES may play a role in the development of T-cell exhaustion, as described before [ 45 ]. It directly induces IFN-γ and cytotoxicity, enhances IL-10, and antagonizes alternative T-cell fates [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…helper T-cells are unrelated to EOMES + Tr1-like cells, which also produce IL-10 but do not express CCR6 and are probably generated from Th1-cells upon chronic TCR stimulation 40,[42][43][44][45] . Here, we showed that CCR6 + T-cells that lack differentiation markers of established CCR6 + T-cell subsets (CCR6 SP ) and produce IL-10 represent an early stage of Th17 differentiation, since they displayed a TCM phenotype but expressed nevertheless some ROR-t, suggesting that they are pre-committed to a Th17 fate.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, CCR6 + T-cells in AD-HIES patients produced significantly increased levels of IL-10 (Figure 6B). Notably, IL-10 production by CCR6 -T-cells, as well as FOXP3 + Tregs and EOMES + Tr1-like cells 40 was instead comparable in AD-HIES patients and HDs (sFigure 6B). Since CCR6 + T-cells have peculiar stimulation requirements for IL-10 production 41 , we analysed IL-10 production also after stimulation of the TCR of purified T-cell subsets with anti-CD3 antibodies in the presence of IL-2 26 , and upon stimulation of total PBMC with the superantigen SEB, which induces a productive interaction between the TCR and MHC class-II molecules.…”
Section: Residual Ccr6 + T-cells In Ad-hies Patients Contain Th1/17-c...mentioning
confidence: 95%
“…In addition to roles for AHR and c-MAF described above, recent evidence demonstrates the importance of the transcription factor EOMES at mediating Tr1 development, and in particular, at inducing cytotoxic potential among Tr1s [reviewed in ( 83 )]. The majority of evidence to date has not clarified whether Tr1 cells are a distinct differentiation lineage, or simply a transient activation state.…”
Section: Cytotoxic Cd4 T-cells At the Gut Mucosal Surfacementioning
confidence: 99%